1980
DOI: 10.1073/pnas.77.9.5287
|View full text |Cite
|
Sign up to set email alerts
|

Helper virus is not required for in vitro erythroid transformation of hematopoietic cells by Friend virus

Abstract: The Friend polycythemia virus complex (FVP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…Thus, our results support earlier evidence that helper-free SFFV efficiently stimulates polyclonal proliferation and differentiation of infected BFU-E erythroblasts (1,3,8,41,42). This mitogenic stimulation of BFU-E apparently requires expression of the SFFV env gene product gp55 on the surfaces of infected cells (13).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, our results support earlier evidence that helper-free SFFV efficiently stimulates polyclonal proliferation and differentiation of infected BFU-E erythroblasts (1,3,8,41,42). This mitogenic stimulation of BFU-E apparently requires expression of the SFFV env gene product gp55 on the surfaces of infected cells (13).…”
Section: Discussionsupporting
confidence: 91%
“…Affected cell populations containing transforming DNA expanded out of control and caused a fulminating disease. Previous work in vitro with helper-deficient virus preparations suggested that SFFV alone can transform hematopoietic cells (18), an observation that is extended by our experiments in vivo. It is now clear that the oncogenic potential of SFFV can be realized without the spread of virus and recruitment of cells.…”
supporting
confidence: 81%
“…It might be required for early SFFV replication to ensure the establishment of rapid erythroleukemia. Previous studies in other laboratories revealed that the defective SFFV alone was able to induce erythroleukemia in adult mice after a long latent period of infection (Eckner and Hettrick, 1979) and helper F-MuLV is not required for in vitro erythroid transformation by SFEV (Hankins and Krantz, 1980). Last but not least, the present studies support the notion that FV-induced erythroleukemia is a multistage disease: an early phase characterized by proliferative effects on erythroid progenitor cells and a later phase characterized by the presence of truly malignant FV-transformed cells (Levy et al, 1979;Tambourin et al, 1979).…”
Section: Discussionmentioning
confidence: 97%